Exposure to di (2-ethylhexyl) phthalate causes locomotor increase and anxiety-like behavior via induction of oxidative stress in brain. (12th February 2023) - Tang, Shixin; Zhang, Hongyang; Xia, Yinyin; Luo, Shiyue; Liu, Yijun; Duan, Xinhao; Zou, Zhen; Chen, Chengzhi; Zhou, Lixiao; Qiu, Jingfu
Abstract: Di (2-ethylhexyl) phthalate (DEHP) is one of the most prevalent xenoestrogen endocrine disruptor in daily life. A growing number of studies showed that DEHP could exhibit long-term adverse health effects on the human body, particularly in the liver, kidneys, heart and reproductive systems. However, the impact of oral intake of DEHP on the nervous system is extremely limited. In the present study, the adult C57BL/6J male mice were intragastrically administered with two dosages of DEHP for 35 days. The behavioral parameters were assessed using the elevated plus maze and open-field test. The mRNA expression levels of neuropeptides and the oxidative stress-associated proteins were detected by qPCR and western blot seperately. The histopathologic alterations of the brain were observed by H&E and Nissl staining. The results demonstrated that DEHP exposure could result in neurobehavioral impairments such as locomotor increase and anxiety-like behavior. Furthermore, pathological damages were clearly observed in the cerebral cortex and hippocampus, accompanied by a decrease in neuropeptides and an increase in oxidative stress, which were all positively correlated with the dose of DEHP. Together, these findings provide valuable clues into the DEHP-induced neurotoxicity.